Effects of native and non-native shade trees on insect predation pressure on Kenyan coffee farms - Ximena Oviedo Moura; Julie A. Jedlicka; Samuel Lopes Oliveira; Matthew D. Johnson (Frontiers in Conservation Science)
IntroductionAgroecosystem practices that aim to increase biodiversity and ecosystem services have the potential to benefit both wildlife and farmers. Shade-coffee systems are well-studied in the Neotropics, but less is known about the relationships among farm management, biodiversity, and ecosystem services in East Africa, where the most commonly used shade trees are native Cordia africana and non-native Grevillea robusta. Ecological theory and empirical evidence suggests that native shade trees should harbor more insects and insectivorous birds than non-native trees, which could translate to more pronounced pest control services on the coffee crop grown below.MethodsWe used artificial plasticine “caterpillars” in a sentinel pest experiment to test the prediction that predation is higher on coffee shrubs near native Cordia than non-native Grevillea shade trees.ResultsWe found that there was no significant effect of tree species on bird predation, while predation by arthropods and total predation (birds + arthropods + unknown) was higher near Grevillea than Cordia.DiscussionWhile unexpected, these results demonstrated that predators readily attacked sentinel pests on coffee shrubs under both shade tree species. The two tree species may balance and complement each other in attracting avian and arthropod ecosystem providers, with Grevillea attracting arthropod predators and generalist birds, and Cordia attracting insectivorous specialists.